Monitoring and Its Influence on the Learning Process of High School Students in Improving Knowledge: A Comprehensive Study - Susanto, Ratnawati; Hapudin, Muhammad Soleh; Simorangkir, Sahat T.; Nasution, Evi Syafrida (FKIP Universitas Lampung, 2024)
Abstract: Clinical Supervision to Improve Teachers Teaching Performance in Secondary Schools: A Comprehensive Study. Objective: This study aims to evaluate the effect of clinical supervision on the teaching performance of teachers in secondary schools. Method: Quantitative research method with a combination of teaching and learning observation instruments and adapted from all school assessments. The subjects were 43 secondary school teachers. Data collection techniques use observation instruments. This instrument was developed from indicators used as a tool to measure teacher performance. The instrument is given a score from point 1 to point 5. The analysis technique uses SPSS Version 25.0 with measurements based on Learning Plans, induction tools, material delivery, questioning techniques, student involvement, reinforcement, training and student assignments, checking training and student assignments, closing learning, and classroom management before and after clinical supervision. Findings: The findings of this research help teachers in schools to know the strengths and weaknesses when teaching is delivered in class. Clinical supervision also helps teachers improve the teaching and learning process more effectively. Clinical supervision can also be used as a guide for high school students to increase their knowledge. Conclusion: Clinical supervision has a significant positive impact on teachers' teaching performance in secondary schools. Keywords: clinical supervision, teaching performance, secondary school management.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202438